Effect of thermoelectric cooler (TEC) integrated at the base of opaque photovoltaic (PV) module to enhance an overall electrical efficiency. (15th May 2018) - Dimri, Neha; Tiwari, Arvind; Tiwari, G.N.
Highlights: TEC module is integrated to opaque PV module for increased electrical efficiency. Thermal model has been derived for opaque PV-TEC collector with and without duct. Experimental study of opaque PV-TEC collector partially covered with TEC is performed. Performance is evaluated in terms of electrical energy, thermal energy and exergy gain. Abstract: In this paper, an opaque photovoltaic integrated thermoelectric cooler (PV-TEC) collector has been proposed, wherein thermoelectric (TEC) module is integrated at the base of opaque photovoltaic (PV) module for the enhancement of an overall electrical efficiency. A thermal model has been derived for opaque PV-TEC collector with and without air duct. The effect of packing area of TEC module has been analyzed for the opaque PV-TEC collector without air duct by considering two cases: [case (a)] partially covered with TEC and [case (b)] fully covered with TEC. Further, an experimental investigation of opaque PV-TEC collector without air duct partially covered with TEC [case (a)], for Buraidah, Saudi Arabia has been carried out. The experimental setup comprises of an opaque photovoltaic module integrated with 36 TEC modules, each having an area of 4 cm × 4 cm. The results indicate a fair agreement between theoretical and experimental values of solar cell temperature (r = 0.916, e = 8.41) and TEC bottom-end temperature (r = 0.981, e = 12.5) for opaque PV-TEC collector partially covered with TEC without air duct [case (a)]. Also, the overall electrical energy gains of [case (a)] opaque PV-TEC collector partially covered with TEC without air duct and [case (b)] opaque PV-TEC collector fully covered with TEC without air duct have been computed, theoretically. The results illustrate that the overall electrical efficiency of [case (b)] is higher than [case (a)] by 4.46–6.23%. The opaque PV-TEC collector without air duct generates only electrical energy, whereas the opaque PV-TEC collector with air duct produces both thermal and electrical energy. Finally, the derived thermal model has been used to evaluate the performance of opaque PV-TEC collector with air duct in terms of thermal gain, electrical gain and overall exergy gain.